Green Materials for Energy, Products and Depollution - Lichtfouse, Eric; Schwarzbauer, Jan; Robert, Didier (Environmental Chemistry for a Sustainable World, 2013)
Using renewable fuels and materials, drinking clean water and food, and breathing safe air are major issues for a sustainable world. This book reviews biodiesel production from microalgae, a promising energy source that does not compete with food production. Several advanced techniques to clean polluted waters, such as electrochemistry, ferrites photocatalysis and low-cost filtration are presented. Chapters also show various living organisms used as bioindicators of toxic metals. Decreasing ecotoxicity of pesticides using suitable surfactants is reviewed. The last chapter evidences new pollutants in urban soils, halogenated polycyclic aromatic hydrocarbons.